The Influence of Educational Marketing on the Image of Islamic Senior High Schools in Bengkalis - Bantan District - Indra; Andriesgo, Johan (Institut Agama Islam Al-Aziziyah Samalanga, 2024)
This research consists of two variables, namely educational marketing (X) and madrasah image (Y). This study aims to find out firstly the marketing of madrasah aliyah education in Bengkalis-Bantan District, second to find out the image of madrasah aliyah in Bengkalis-Bantan District, third to determine the influence of education marketing on the image of madrasah aliyah in BengkalisBantan District. The type of research carried out is Field Research where the research is carried out with How to go directly into the field to obtain data and analyze data. While the research approach used is quantitative descriptive where to get results obtained by analysis through SPSS as a measurement. The subjects in this study were parents/guardians of madrasah aliyah students in BengkalisBantan District. The object of this study is the influence of educational marketing on the image of madrasah aliyah in Bengkalis – Bantan District. The population I took In this study, there were 43 parents/guardians of students. While the data collection technique is by using questionnaires, interviews and documentation. The result of this study is that the marketing of education is very influential on the image of madrasah aliyah in Bengkalis-Bantan District, because after being tested from the questionnaire that has been distributed, it is then processed at SPSS using a correlation test obtained a value of 0.725 which is in the range of 0.70 – 0.90 which means between variable X and variable Y there is a high correlation. While the value of significance obtained is 0.000, which means there is an influence.